We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
106
1
avatar

please help thanks

 May 11, 2019

Best Answer 

 #1
avatar+6008 
+1

\(3x+1 = 3(x-2) + 7\\ \dfrac{3x+1}{x-2}=\dfrac{3(x-2)+7}{x-2} = 3 + \dfrac{7}{x-2}\\ A=3\\ B=7\)

.
 May 11, 2019
 #1
avatar+6008 
+1
Best Answer

\(3x+1 = 3(x-2) + 7\\ \dfrac{3x+1}{x-2}=\dfrac{3(x-2)+7}{x-2} = 3 + \dfrac{7}{x-2}\\ A=3\\ B=7\)

Rom May 11, 2019

33 Online Users

avatar
avatar